Method for extracting iron and silicon from copper tailings to synthesize arsenic adsorption composite microspheres through self-assembly and application of arsenic adsorption composite microspheres
By extracting iron and silicon from copper tailings, Fe-mSiO2/SA composite microspheres are solved, and the cost of pentavalent arsenic pollution treatment in groundwater is high, expensive materials and narrow application scope, achieving high efficiency, economical and repeatable The arsenic removal effect is utilized.
Patent Information
- Application Number
- CN202411340231.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as high cost, expensive materials, narrow application scope and difficulty in recycling when dealing with pentavalent arsenic pollution in groundwater. Especially under the conditions of weak acidic water quality and low calcium content, the economical and easy nature of traditional adsorbents. Inadequate reusability.
Iron and silicon were extracted from copper tailings, mesoporous silica and iron oxides were prepared by cross-linking of sodium alginate, and Fe-mSiO2/SA composite microspheres were formed as adsorbents, which used their high specific surface area and stability to improve arsenic and remove through chemical adsorption mechanism.
It has achieved efficient removal of pentavalent arsenic in groundwater within a wide pH range, reduced treatment costs, avoided secondary pollution, and had the characteristics of reusable use, and is suitable for a variety of groundwater conditions.
Smart Images

Figure BDA0005059473100000061 
Figure BDA0005059473100000081 
Figure BDA0005059473100000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of arsenic removal in water bodies, and specifically relates to a method for extracting iron and silicon from copper tailings to synthesize arsenic-adsorbing composite microspheres through self-assembly and application thereof. Background Art
[0002] Due to geological tectonic movements (volcanic eruptions, rock weathering, etc.), human activities (industrial production, agricultural production) and other environmental factors, arsenic and its compounds have penetrated into the aquatic environment, posing a huge threat to natural ecosystems and human health. Arsenic pollution can cause serious harm to humans or plants, and is persistent, difficult to degrade and accumulative. Long-term exposure to a high-arsenic environment can lead to various cancers and cardiovascular diseases. Arsenic is easily enriched in groundwater and soil and enters the human body through the food chain, affecting human health. With the continuous development of my country's industry, arsenic pollution caused by non-ferrous metal smelting has seriously affected the normal lives of residents, so the treatment of arsenic in groundwater is imminent.
[0003] Arsenic in groundwater exists in trivalent arsenic and pentavalent arsenic, of which trivalent arsenic only accounts for a small part, and trivalent arsenic is easily oxidized to pentavalent arsenic in water. The arsenic explored in this invention mainly treats pentavalent arsenic in groundwater. GB 5749-2006 "Sanitary Standards for Drinking Water" promulgated in 2006 reduces the maximum concentration standard of pentavalent arsenic in drinking water from 0.05mg / L to 0.01mg / L. The main methods for treating arsenic pollution in water include precipitation, electrocoagulation, membrane separation, adsorption, etc. Among them, the precipitation method mainly adjusts the pH of the solution by adding strong alkali to generate calcium arsenate precipitation for filtration and removal. The precipitation method has a low cost, and excessive reagents need to be added during operation, which will seriously affect the quality of groundwater, and the treatment is not thorough. The precipitation method is mainly used for the treatment of industrial wastewater; the electrocoagulation method has too high requirements for technical operation, and the treatment effect is closely related to the electrode material. The electrode needs to be replaced frequently, and the actual application cost is high; the membrane separation method has high requirements for water quality and is more advantageous in treating water bodies with less impurities and small amounts. As for the treatment of arsenic in groundwater, adsorption is the most practical method. The adsorption method is economical, highly selective and has good treatment effect. In addition, the adsorbent will not increase the salt content in the water during the treatment process. The spherical adsorption material overcomes the problem of difficult recovery of powdered adsorbents in the past, and has a certain degree of reusability. It is an adsorption material with broad application prospects.
[0004] CN107824163A discloses a MIL-125 (Ti) / chitosan composite microsphere for adsorbing arsenic, wherein the weight ratio of modified chitosan to MIL-125 (Ti) in the composite microsphere is 1:0.8-1.2. Chitosan is modified with ferric chloride, then cross-linked with glutaraldehyde, washed, dried, and ground to obtain modified chitosan; tetrabutyl titanate, terephthalic acid, N, N-dimethylformamide and methanol are mixed evenly, and MIL-125 (Ti) is reacted in a high-pressure reactor; MIL-125 (Ti) is dissolved in deionized water, and modified chitosan is added after dissolution, stirred, and then dripped into a sodium tripolyphosphate solution, stirred and solidified to obtain composite microspheres. The composite microspheres have good dispersibility, regular sphericity, high adsorption capacity and faster adsorption rate, strong ability to adsorb arsenic, and strong reusability. However, this adsorbent is only suitable for use under photocatalytic conditions and utilizes expensive Ti metal, which results in expensive material preparation and is not economical.
[0005] CN110143661A discloses a method for removing arsenic from calcium-rich high-arsenic groundwater with biochar, which is to directly add biochar to calcium-rich alkaline high-arsenic groundwater, and after stirring for a period of time, use the oxidative active groups on the surface of biochar to oxidize trivalent arsenic in groundwater to high-valent pentavalent arsenic, and the generated arsenate forms arsenic-calcium-biochar precipitation with calcium ions and biochar to remove dissolved arsenic in the water body. The invention has low processing cost, high efficiency, and no secondary pollution. However, it can only be applied to specific high-arsenic water bodies with high calcium concentration (20-2000mg / L) and pH range of 8-13. The pH of groundwater is generally around 7.5 after silicate filtration. In areas with highly concentrated population, it is difficult to filter through silicates. The pH of groundwater is generally between 5-6, and the water quality is generally weakly acidic. This method is not applicable to the treatment of arsenic pollution in most groundwater. At the same time, the material of this method is powder, which is expensive when recycled, which is not conducive to recycling. Summary of the invention
[0006] In view of the shortcomings of existing arsenic pollution treatment technology in groundwater, the purpose of the present invention is to provide a method and application of extracting iron and silicon from copper tailings to synthesize composite microspheres for arsenic adsorption by self-assembly. The method of the present invention uses iron and silicon in copper tailings to crosslink with sodium alginate to synthesize composite microspheres Fe-mSiO2 / SA (FSA), which are used as adsorbents for the removal of arsenic in groundwater. The mesoporous silica (mSiO2) prepared by extracting silicon from copper tailings has a highly ordered hexagonal mesoporous structure, and the iron element extracted from the copper tailings is uniformly dispersed on mSiO2 to obtain a Fe-mSiO2 composite material, which mainly exists in the form of α-FeOOH and β-FeOOH. Fe-mSiO2 is crosslinked with sodium alginate to synthesize composite microspheres FSA, which not only has good stability, but also has a high specific surface area, so that more adsorption active sites can be provided. The adsorbent prepared by the method of the present invention not only improves the adsorption capacity of iron and silicon to arsenic, but also does not produce secondary pollution, and at the same time has the function of being reusable, reduces the removal cost, and has a wide range of application prospects.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for extracting iron and silicon from copper tailings to self-assemble and synthesize arsenic-adsorbing composite microspheres comprises the following steps:
[0009] (1) copper tailings and sulfuric acid solution were mixed at a solid-liquid ratio of 1 g:10 mL, heated and stirred at 95-105° C. for 4-6 h, heating was stopped, an appropriate amount of ultrapure water was added, stirring was continued for 2-3 h, and iron source solution and acid-insoluble solid residue were obtained by suction filtration;
[0010] (2) Using the acid-insoluble solid residue obtained in step (1) to prepare mesoporous silica (mSiO2):
[0011] S1: washing the acid-insoluble solid residue with water until it becomes neutral, and drying it to obtain high-silicon slag;
[0012] S2: Mix high silicon slag, block NaOH and ultrapure water and place them in a high pressure reactor, heat at 155-165°C for 8-9h, filter after the reaction, and take the filtrate, i.e., Na2SiO3 solution;
[0013] S3: Mix the filtrate with an aqueous solution of hexadecyltrimethylammonium bromide, adjust the pH value of the solution to 10 with an acid, then place the mixture in a high-pressure reactor and heat the mixture at 110-120°C for 20-24 hours. After the reaction is completed, filter the mixture, wash it with water until it is neutral, wash it with alcohol, and dry it to obtain a white powder. Place the white powder in a muffle furnace and calcine it at 550°C for 7 hours to obtain mesoporous silica (mSiO2).
[0014] (3) preparing iron oxide using the iron source solution obtained in step (1):
[0015] Add H2O2 solution dropwise to the iron source solution to remove the Fe 2+ Completely oxidized to Fe 3+ , then add ammonia water to adjust the pH value of the solution to 3.6-3.8, stir at room temperature for 0.5-1h, filter to obtain a brick red solid, and dry to obtain iron oxide;
[0016] (4) Preparation of Fe-mSiO2 composite materials:
[0017] Iron oxide and mesoporous silica were added to dilute hydrochloric acid in a mass ratio of 4:3, respectively, ultrasonicated for 5 minutes, stirred at room temperature for 2-3 hours, filtered, and dried to obtain a light yellow powder, namely, Fe-mSiO2 composite material;
[0018] (5) Preparation of Fe-mSiO2 / SA composite microspheres:
[0019] Add the Fe-mSiO2 composite material into ultrapure water to obtain a 1.5w / v% Fe-mSiO2 mixed solution, and dissolve sodium alginate (SA) in ultrapure water to obtain a 2.5w / v% SA solution; add the SA solution dropwise into the Fe-mSiO2 mixed solution under constant stirring, stir for 1.5-2h to obtain gel beads, wash with water until neutral, and freeze-dry to obtain Fe-mSiO2 / SA composite microspheres.
[0020] Furthermore, in step (1), the copper tailings are sieved through a 100-mesh sieve.
[0021] Furthermore, in step (1), the concentration of the sulfuric acid solution is 4-5 mol / L.
[0022] Furthermore, in step (1), the volume of ultrapure water added is 500 mL for every 10-15 g of copper tailings.
[0023] Furthermore, in step (2), high silicon slag, block NaOH and ultrapure water are mixed in a ratio of 9 g:10 g:120 mL.
[0024] Furthermore, in step (4), the concentration of dilute hydrochloric acid is 0.1-0.5 mol / L.
[0025] Furthermore, in step (4), the ultrasonic power is 200W.
[0026] Furthermore, in step (4), the iron element in the Fe-mSiO2 composite material is uniformly loaded on the mesoporous silica to form a stable iron complex, and the iron element coexists in the form of γ-Fe3O4, α-FeOOH and β-FeOOH.
[0027] Further, in step (5), the SA solution is added dropwise into the Fe-mSiO2 mixed solution at a volume ratio of 8:100.
[0028] Furthermore, in step (5), sodium alginate contains abundant hydroxyl and carboxyl functional groups, which are easy to react with metal cations (Fe 3+ ) cross-linked to form a three-dimensional network structure. The obtained Fe-mSiO2 / SA composite microspheres are three-dimensional spherical with a diameter of 2-3mm.
[0029] Furthermore, the drying conditions are: drying at 60°C for 12 hours.
[0030] An application of Fe-mSiO2 / SA composite microspheres obtained by the above method in removing As(V) from As(V)-containing wastewater.
[0031] Furthermore, the temperature of the As(V)-containing wastewater is 20°C-50°C, preferably 20°C-30°C, and most preferably 25°C.
[0032] Furthermore, before the Fe-mSiO2 / SA composite microspheres are added to the wastewater containing As(V), the pH value of the wastewater is adjusted to 3-11.
[0033] Furthermore, the initial concentration of As(V) in the As(V)-containing wastewater ranges from 0.1 to 50 mg / L.
[0034] Furthermore, after the Fe-mSiO2 / SA composite microspheres are added into wastewater containing As(V), the adsorption time is 1-720 min.
[0035] The main mechanism of arsenic adsorption by Fe-mSiO2 / SA composite microspheres is: Fe-mSiO2 / SA composite microspheres contain abundant mesopores as well as more hydroxyl groups and macropores. Due to the protonation of hydroxyl groups, hydroxyl groups complex with arsenate on the interface to form stable monodentate or bidentate complexes. Fe-mSiO2 / SA composite microspheres undergo complexation reaction with As(V), and As(V) on the surface of FSA-As(V) is reduced to As(III) under oxygen-rich conditions. The pores in Fe-mSiO2 / SA composite microspheres provide additional physical adsorption promotion effect during the adsorption process, thereby adsorbing to the surface of the material to achieve the purpose of water purification.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] (1) The present invention uses industrial solid waste - copper tailings as the matrix material, uses acid leaching to extract silicon and iron elements step by step to prepare mesoporous silica and iron oxide, and introduces sodium alginate rich in hydroxyl and carboxyl groups for cross-linking to synthesize Fe-mSiO2 / SA composite microspheres with good adsorption performance for As(V). The present invention provides a simple, green, environmentally friendly, and economical modification method, which successfully modifies the spherical material to prepare a new adsorbent with good arsenic removal effect;
[0038] (2) The Fe-mSiO2 / SA composite microsphere adsorbent prepared by the present invention will not produce new pollutants during the treatment of groundwater, thus avoiding secondary pollution to the environment and being safe and reliable;
[0039] (3) The Fe-mSiO2 / SA composite microsphere adsorbent prepared by the present invention has a very good removal effect on arsenic, has a wide pH range of water (pH = 3-11), is not greatly affected by temperature (20°C-50°C), and the entire adsorption process is mainly chemical adsorption and is spontaneous. When the initial concentration of As(V) solution is 50 mg / L, the adsorbent dosage is 0.6 g / L, and the temperature is 25°C, the adsorption time is 1 min, the adsorption capacity is 70.94 mg / g, and the As(V) removal rate is 84.41%; the adsorption time is 5 min, the adsorption capacity is The adsorption capacity was 71.58 mg / g, and the As(V) removal rate was 85.17%; the adsorption time was 30 min, the adsorption capacity was 77.07 mg / g, and the As(V) removal rate was 91.76%; the adsorption time was 60 min, the adsorption capacity was 78.93 mg / g, and the As(V) removal rate was 93.99%; the adsorption time was 120 min, the adsorption capacity was 80.20 mg / g, and the As(V) removal rate was 95.28%; the adsorption time was 720 min, the adsorption capacity was 82.36 mg / g, and the As(V) removal rate was 98.11%;
[0040] (4) The Fe-mSiO2 / SA composite microsphere adsorbent prepared by the present invention can be regenerated after desorption with 0.5 mol / L HCl solution, has the characteristics of being reusable, has good economic benefits and important practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a graph showing the effect of the initial dosage of FSA prepared in Example 1 on the As(V) adsorption performance.
[0042] Figure 2 This is a graph showing the effect of initial pH on the As(V) removal performance of FSA prepared in Example 1.
[0043] Figure 3This is a graph showing the effect of adsorption temperature on the As(V) removal performance of FSA prepared in Example 1.
[0044] Figure 4 This is a diagram showing the effect of coexisting ions on the As(V) removal performance of FSA prepared in Example 1.
[0045] Figure 5 The figure (a) shows the effect of adsorption time on the performance of FSA prepared in Example 1 in removing As(V) and different kinetic fitting models (bd) of FSA adsorbing As(V). Among them: (b) is a pseudo-first-order kinetic model; (c) is a pseudo-second-order kinetic model; (d) is an intra-particle diffusion model.
[0046] Figure 6 This is the FT-IR spectra of mSiO2, Fe-mSiO2 and FSA prepared in Example 1 before and after adsorption of As(V).
[0047] Figure 7 It is the XRD spectra of mSiO2, Fe-mSiO2 and FSA prepared in Example 1 before and after adsorption of As(V).
[0048] Figure 8 This is the XPS spectra of mSiO2, Fe-mSiO2 and FSA prepared in Example 1 before and after the adsorption of As(V).
[0049] Fig. 9 The SEM, TEM, AFM and EDS spectra of the adsorbent prepared in Example 1. In which: (a) Figures 1-3 are respectively: 1-mSiO2 SEM, 2-mSiO2 TEM, 3-Fe-mSiO2 SEM; (b) Figures 1-7 are respectively: 1-FSA SEM (1 mm scale), 2-FSA SEM (2 μm scale), 3-FSA AFM, 4-7-FSA EDS. DETAILED DESCRIPTION
[0050] The applicant will further explain the present invention in detail below with reference to specific embodiments. The embodiments are only used to help understand the present invention, but the protection scope of the present invention is not limited thereto.
[0051] The copper tailings used in the embodiment were provided by a copper smelter in Huangshi City, Hubei Province, and its main chemical components are as follows:
[0052]
[0053] The copper tailings used in the examples were first dried in an oven at 80° C., and then pre-treated by passing through a 100-mesh (aperture 0.15 mm) sieve for later use.
[0054] Example 1: A method for extracting iron and silicon from copper tailings to synthesize arsenic-adsorbing composite microspheres by self-assembly
[0055] (1) Pour 15 g of copper tailings through a 100-mesh sieve into a 1000-mL beaker, and then add 150 mL of 5 mol / L H2SO4; place the beaker in an oil bath at 100°C and heat with stirring for 5 h; after heating, slowly add 500 mL of ultrapure water to the beaker and continue stirring for 3 h; use a vacuum pump to filter to obtain an iron source solution and an acid-insoluble solid residue.
[0056] (2) All the acid-insoluble solid residues obtained in step (1) are repeatedly washed with distilled water until neutral, and then dried at 60°C for 12 hours to obtain high-silicon slag (9g). The obtained 9g high-silicon slag, 10g block NaOH and 120mL ultrapure water are mixed and placed in a high-pressure reactor, and heated at 160°C for 9 hours. After the reaction, the suspension is filtered and the filtrate is taken, which is the extracted Na2SiO3 solution. It can be used as a silicon source to synthesize mesoporous silica. The specific steps are: 1g hexadecyltrimethylammonium bromide (CTAB) is dissolved in 50mL ultrapure water, after ultrasonication for 5 minutes, 10mL CTAB aqueous solution is measured, the extracted Na2SiO3 solution is added thereto, and stirred for 1 hour, and then HCl solution is added thereto to adjust the pH value of the solution to 10, and then stirring is continued for 2 hours. After the stirring is completed, the obtained white suspension is heated in a high-pressure reactor at 110°C for 24 hours. After the reaction, the product was filtered, washed with water until neutral, and then washed twice with anhydrous ethanol. The product was dried at 60°C for 12 h to obtain a white powder solid, which was then calcined at 550°C for 7 h to remove the CTAB template to obtain mesoporous silica, abbreviated as mSiO2.
[0057] (3) Add 10 mL of 30 wt% H2O2 solution dropwise to the iron source solution obtained in step (1) (to make Fe 2+ Oxidized to Fe 3 + ), and then adjusting the pH value of the solution to 3.7 by dropping 25 wt % ammonia water, stirring at room temperature for 1 hour, and filtering to obtain a brick red solid, which was dried at 60° C. for 12 hours to obtain iron oxide.
[0058] (4) Weigh 2 g of the iron oxide obtained in step (3) and dissolve it in 50 mL of 0.1 mol / L dilute hydrochloric acid solution, then add 1.5 g of mSiO2 obtained in step (2), ultrasonicate at 200 W for 5 min, stir at room temperature for 2 h, filter, and dry at 60 ° C for 12 h to obtain a light yellow powdery Fe-mSiO2 composite material, abbreviated as Fe-mSiO2.
[0059] (5) Weigh 1.5g of the Fe-mSiO2 powder obtained in step (4) and add it to 100mL of ultrapure water, stir evenly, and obtain a 1.5w / v% Fe-mSiO2 mixed solution; dissolve 2.5g of sodium alginate (SA) in 100mL of ultrapure water, stir in a water bath at 65°C for 1.5h, and obtain a 2.5w / v% SA solution. Use a 10mL syringe to draw 8mL of SA solution, drip it dropwise into the Fe-mSiO2 mixed solution and stir continuously for 2h. After stirring, rinse the gel beads with ultrapure water several times until neutral. The rinsed gel beads are placed in a -80°C refrigerator and frozen for 12h, and then placed in a -50°C freeze dryer and dried for 12h to obtain Fe-mSiO2 / SA composite microspheres (abbreviated as FSA). The surface of the formed beads is not only smooth but also round and not easy to break.
[0060] Comparative Example 1
[0061] The method of this comparative example 1 is the same as that of the embodiment 1, the only difference being that a different spheroidizing medium is selected in the spheroidizing process in step (5).
[0062] In the ball-forming process of step (5), if the concentration of the sodium alginate solution is too dilute (e.g., 2.0 w / v%) or too viscous (e.g., 3.0 w / v%), it is not conducive to ball-forming. When the concentration of the sodium alginate solution is too dilute, the sodium alginate solution and the Fe-mSiO2 mixed solution stick together and cannot form a ball; when the concentration of the sodium alginate solution is too viscous, it makes it difficult to add the solution dropwise.
[0063] In addition, chitosan solution was selected as the sphering medium, and chitosan was dissolved in ultrapure water to prepare a chitosan solution with a concentration of 2.5w / v%. 8mL of chitosan solution was dripped into 100mL of 1.5w / v% Fe-mSiO2 mixed solution with a syringe and stirred continuously for 2h. After stirring, the gel beads were rinsed with ultrapure water several times until neutral. The rinsed gel beads were placed in a -80℃ refrigerator and frozen for 12h, and then placed in a -50℃ freeze dryer and dried for 12h to obtain Fe-mSiO2 / CS composite microspheres. Compared with Fe-mSiO2 / SA composite microspheres, the spheres of Fe-mSiO2 / CS composite microspheres are not round, and they will break if touched lightly by hand.
[0064] Experimental example
[0065] The adsorbent was subjected to a heavy metal adsorption experiment. The arsenic solution was prepared by arsenic acid (H3AsO4, 99.9%, AR) and deionized water, and the concentration was calculated as As(V) element. After the adsorbent adsorbed As(V), a sample was taken. After filtering through a 0.45um filter membrane, the concentration of As(V) remaining in the filtrate was measured using ICP-OES (inductively coupled plasma emission spectrometer, Thermo Fisher Scientific). The removal rate of the adsorbent for As(V) was calculated according to formula (1), and the adsorption capacity of the adsorbent for As(V) was calculated according to formula (2).
[0066]
[0067] R: removal rate of As(V) by adsorbent;
[0068] q: adsorption capacity of adsorbent for As(V) (mg / g);
[0069] c0: initial As(V) concentration (mg / L);
[0070] c: residual As(V) concentration after adsorption (mg / L);
[0071] v: volume of As(V) solution (L);
[0072] m: weight of adsorbent added (g).
[0073] 1. The "Fe-mSiO2 composite material" (abbreviated as Fe-mSiO2) prepared in step (4) of Example 1 was used as an adsorbent to carry out a heavy metal adsorption experiment, and the steps are as follows:
[0074] 1) Effect of adsorbent dosage on the performance of adsorbent in removing As(V)
[0075] 50 mL of As(V) solution (pH about 3.5) with an initial concentration of 20 mg / L was measured and poured into a 100 mL conical flask. Then 0.01-0.05 g of adsorbent Fe-mSiO2 was weighed into the conical flask and covered with a sealing film. The flask was shaken at 180 rpm for 12 h in a constant temperature oscillating box at 25 °C. After the adsorption was completed, an appropriate amount of supernatant was drawn with a 10 mL syringe and filtered with a 0.45 μm microporous membrane. The residual concentration of As(V) in the filtrate was determined by ICP-OES. The adsorption capacity and removal rate obtained are shown in Table 1.
[0076] Table 1 Effect of different adsorbent dosage on arsenic adsorption performance
[0077] Dosage / (g) Dosage concentration / (g / L) Adsorption capacity / (mg / g) Removal rate / (%) 0.01 0.2 24.632 23.51 0.015 0.3 28.890 41.37 0.02 0.4 29.334 56.00 0.025 0.5 28.391 67.76 0.03 0.6 29.756 86.99 0.04 0.8 25.675 98.04 0.05 1 20.451 97.61
[0078] It can be seen from Table 1 that when the dosage of adsorbent Fe-mSiO2 is 0.6 g / L, its adsorption capacity and removal rate are relatively optimal.
[0079] 2) Effect of initial pH of As(V) solution on the performance of adsorbent in removing As(V)
[0080] 50 mL of As(V) solution (pH about 3.5) with an initial concentration of 20 mg / L was measured in a 100 mL conical flask. The pH value of the As(V) solution was adjusted to 1-13 using HCl solution and NaOH solution. Then 0.03 g of Fe-mSiO2 was weighed and placed in a conical flask and covered with a sealing film. The flask was shaken at 180 rpm for 12 hours in a constant temperature oscillating box at 25°C. After the adsorption was completed, an appropriate amount of supernatant was drawn with a 10 mL syringe and filtered with a 0.45 μm microporous filter membrane. The residual concentration of As(V) in the filtrate was determined by ICP-OES. The adsorption capacity and removal rate obtained are shown in Table 2.
[0081] Table 2 Effect of initial pH of As(V) solution on arsenic adsorption performance
[0082]
[0083]
[0084] When the solution pH is in the range of 1 to 9, the adsorption capacity of As(V) increases with the increase of pH value, and shows a stable trend in the pH range of 3 to 9, indicating that As(V) may enhance the adsorption capacity through electrostatic effect. When the pH value is > 9, the adsorption capacity decreases rapidly, which can be explained by the fact that metal ions easily form hydroxides in a strong alkaline environment, thereby weakening the adsorption process.
[0085] 2. The "Fe-mSiO2 / SA composite microspheres" (FSA for short) prepared in step (5) of Example 1 were used as adsorbents to conduct heavy metal adsorption experiments, and the steps were as follows:
[0086] 1) Effect of adsorbent dosage on the performance of adsorbent in removing As(V)
[0087] 50 mL of As(V) solution with an initial concentration of 50 mg / L was measured and poured into a 100 mL conical flask. Then 0.01-0.09 g of adsorbent FSA was weighed into the conical flask and covered with a sealing film. It was shaken at 180 rpm for 12 hours in a constant temperature oscillating box at 25°C. After the adsorption was completed, an appropriate amount of supernatant was drawn with a 10 mL syringe and filtered with a 0.45 μm microporous filter membrane. The residual concentration of As(V) in the filtrate was determined by ICP-OES. The adsorption capacity and removal rate obtained are shown in Table 3 and Figure 1 .
[0088] Table 3 Effect of different adsorbent dosage on arsenic adsorption performance
[0089]
[0090]
[0091] It can be seen from Table 3 that when the dosage of adsorbent FSA is 0.6 g / L, its adsorption capacity (76.50 mg / g) and removal rate (96.60%) are relatively optimal. Therefore, the ideal dosage of FSA for subsequent batch adsorption experiments is determined to be 0.6 g / L.
[0092] 2) Effect of initial pH of As(V) solution on the performance of adsorbent in removing As(V)
[0093] 50 mL of As(V) solution with an initial concentration of 50 mg / L was measured and poured into a 100 mL conical flask. The pH value of the As(V) solution was adjusted to 1-13 using HCl solution and NaOH solution. Then 0.03 g of FSA was weighed into the conical flask and covered with a sealing film, and oscillated at 180 rpm for 12 hours in a constant temperature oscillating box at 25°C. After the adsorption was completed, an appropriate amount of supernatant was aspirated with a 10 mL syringe and filtered with a 0.45 um microporous filter membrane. The residual concentration of As(V) in the filtrate was tested by ICP-OES. The obtained adsorption capacity and removal rate are shown in Table 4. The effect of initial pH on the As(V) removal performance of FSA prepared in Example 1 is shown in Table 4. Figure 2 .
[0094] Table 4 Effect of initial solution pH on arsenic adsorption performance
[0095] pH before reaction pH after reaction Adsorption capacity / (mg / g) Removal rate / (%) 1 1 3.16 4.00 3 2.34 77.52 97.89 5 2.45 77.59 97.97 7 2.49 77.32 97.63 9 2.56 77.77 98.20 11 2.95 69.73 95.91 13 12.95 5.53 6.64
[0096] As can be seen from Table 4, the adsorbent has a high removal rate of more than 95% in the initial pH range of 3-11, which shows that this adsorbent has a wide range of applications and is suitable for the removal of arsenic pollutants in most groundwater. The removal rate is low at pH 1.0 and 13.0 because arsenic is desorbed in a strong acid or alkaline environment. Therefore, the adsorbent needs to pay attention to the applicable range of water pH in practical applications.
[0097] 3) Effect of adsorption temperature on the performance of adsorbents in removing As(V)
[0098] 50 mL of As(V) solution with an initial concentration of 50 mg / L was measured and poured into 8 100 mL conical flasks, and then the shaking temperature was adjusted to 20°C, 30°C, 40°C, and 50°C. Subsequently, 0.03 g of FSA was weighed into the conical flasks and covered with sealing film, and oscillated at a constant temperature of 180 rpm for 12 hours. After the adsorption was completed, an appropriate amount of supernatant was drawn with a 10 mL syringe and filtered with a 0.45 um microporous membrane. The residual concentration of As(V) in the filtrate was determined by ICP-OES. The adsorption capacity and removal rate obtained are shown in Table 5 and Figure 3 .
[0099] Table 5 Effect of temperature on arsenic adsorption performance
[0100] Temperature / (℃) Adsorption capacity / (mg / g) Removal rate / (%) 20 72.81 86.74 30 78.18 96.74 40 76.42 91.04 50 74.01 88.18
[0101] It can be seen from Table 5 that within the temperature range of 20℃-50℃, the removal rate of the adsorbent FSA for the solution with an initial arsenic concentration of 50 mg / L is above 85%, and is not greatly affected by temperature changes. This shows that the entire adsorption process is mainly chemical adsorption and occurs spontaneously, and the adsorbent has good adsorption performance.
[0102] 4) Effect of coexisting ions on the performance of adsorbents in removing As(V)
[0103] 50 mL of As(V) solution with an initial concentration of 50 mg / L was measured and poured into 13 100 mL conical flasks. 0.1 mol / L NaCl, NaNO3, Na2SO4, and Na3PO4 solutions were prepared respectively. The prepared coexisting ion solutions were added to the As(V) solutions. The single coexisting ion concentrations in the As(V) solutions were 0.05 mmol / L, 0.1 mmol / L, and 0.2 mmol / L, respectively. A group without any coexisting ions was kept as a blank control. Subsequently, 0.03 g of FSA was weighed into conical flasks and covered with sealing film. The flasks were shaken at 180 rpm in a constant temperature shaking box at 25°C for 12 hours. After the adsorption was completed, an appropriate amount of supernatant was drawn with a 10 mL syringe and filtered with a 0.45 um microporous filter membrane. The residual concentration of As(V) in the filtrate was determined by ICP-OES. The adsorption capacity obtained is shown in Figure 4 , the removal rates are shown in Table 6.
[0104] Table 6 Effect of competing ions on arsenic adsorption performance
[0105]
[0106] As can be seen from Table 6, phosphate has a greater impact on the adsorption process of arsenic, especially high-concentration phosphate ions. This is because arsenic and phosphorus belong to the same main group elements, have similar structures, and occupy the adsorption active sites of arsenic by the adsorbent. In practical applications, the concentration of competing ions in groundwater will not be too high, and low-concentration anions will not affect the adsorption of arsenic. Therefore, the adsorption of arsenic in groundwater by adsorbents still has certain practical significance.
[0107] 5) Effect of adsorption time on the performance of adsorbents in removing As(V)
[0108] 50 mL of As(V) solution with an initial concentration of 50 mg / L was measured and poured into two 100 mL conical flasks, and then 0.03 g of FSA was weighed into the conical flasks and covered with sealing film, and oscillated at 180 rpm for 720 min in a constant temperature oscillating box at 25 °C. Samples were taken with a syringe at 1 min, 3 min, 5 min, 10 min, 20 min, 30 min, 45 min, 60 min, 90 min, 120 min, 180 min, 240 min, 300 min, 360 min, 480 min, 600 min, and 720 min, respectively. After filtering through a 0.45 um microporous membrane, the residual concentration of As(V) in the filtrate was measured by ICP-OES. The adsorption capacity and removal rate obtained are shown in Table 7 and Figure 5 .
[0109] Table 7 Effect of adsorption time on arsenic adsorption performance
[0110] Adsorption time / (min) Adsorption capacity / (mg / g) Removal rate / (%) 1 70.9433 84.41 3 71.2538 84.78 5 71.5807 85.17 10 74.4733 88.64 20 75.7658 90.19 30 77.0702 91.76 45 77.9108 92.76 60 78.9275 93.99 90 79.1487 94.25 120 80.2042 95.28 180 80.8222 96.26 240 81.0200 96.50 300 81.0272 96.51 360 81.4907 97.06 480 81.9423 97.60 600 81.9423 97.61 720 82.3652 98.11
[0111] As can be seen from Table 7, within 0-60min, the adsorption rate increases rapidly, and then the adsorption rate increases slowly until the adsorption equilibrium is reached at 240min. According to the kinetic fitting results, it can be seen that the adsorption of arsenic by the material is more in line with the pseudo-second-order kinetic model, indicating that the adsorption process of arsenic on FSA is mainly chemical adsorption. The short initial equilibrium time and high adsorption efficiency indicate that the active sites on the adsorbent surface are dense and have a good adsorption effect.
[0112] In order to understand the adsorption rate and control process of As(V) by Fe-mSiO2 / SA composite microspheres, the effect of contact time on As(V) adsorption was studied, and the pseudo-first-order, pseudo-second-order and intra-particle diffusion models were used to explore the adsorption kinetics of microsphere adsorbents, providing valuable insights into the factors controlling the adsorption mechanism at the solid-liquid interface. Figure 5 As shown in the figure, (a) is the effect of contact time on the removal of As(V); (b) is the pseudo-first-order kinetic model of Fe-mSiO2 / SA adsorption of As(V); (c) is the pseudo-second-order kinetic model of Fe-mSiO2 / SA adsorption of As(V); (d) is the intra-particle diffusion model of Fe-mSiO2 / SA adsorption of As(V). Figure 5 It can be seen that the q calculated by the pseudo-second-level model is e The value is more consistent with the experimental data, and the correlation coefficient R 2 The value (0.9996 to 0.9999) is also higher than the R 2The value (0.7859~0.9873) is better fitted. This indicates that the adsorption process is mainly chemical adsorption, that is, As(V) is adsorbed through chemical bonds and complex reactions between the adsorbent and the adsorbate. It is worth noting that with the increase of the initial As(V) concentration, the k2 value of the pseudo-second-order kinetic model decreases, which indicates that mass transfer limitations may occur at high concentrations, that is, the rate at which As(V) is transferred from the solution to the surface of the microsphere adsorbent will be limited. Further, this study selected the experimental condition of an initial As(V) concentration of 50 mg / L, which not only helps to evaluate the adsorption performance of Fe-mSiO2 / SA adsorbent for As(V), but also better verifies its applicability and feasibility in treating high-concentration As(V) contaminated water bodies in practical applications. As the reaction proceeds, the adsorption capacity gradually increases with time until it reaches a stable state of adsorption saturation. The adsorption rate changes from rapid adsorption in the initial stage to a stable stage thereafter, which may be due to the fact that the empty surface sites of the microsphere adsorbent have been filled, and it is difficult to be occupied under the repulsive force of the solute molecules, resulting in saturation of the adsorption process. For spherical adsorbents, mass transfer in the sphere is the key factor affecting the adsorption process. Therefore, the internal diffusion model can also be used to understand the rate-limiting step of the adsorption rate. Figure 5 (d) shows that the adsorption process is divided into three stages: first, As(V) is rapidly adsorbed from the solution to the surface of the microspheres by electrostatic adsorption, which is the result of the combined action of surface contact mass transfer and internal diffusion; second, as the adsorption process proceeds, As(V) begins to slowly diffuse into the pores of the microspheres and is adsorbed on the inner surface of the adsorbent; finally, the As(V) concentration inside and outside the particles remains basically stable, and the adsorption process enters the dynamic equilibrium stage. In addition, the linear fitting curve does not pass through the origin, which further confirms that the internal diffusion mechanism of the particles is not the only rate-limiting step in the As(V) adsorption process.
[0113] 6) Repeated experiments on materials
[0114] The "Fe-mSiO2 / SA composite microspheres" (FSA for short) prepared in step (5) of Example 1 were used as adsorbents. 50 mL of As(V) solution with an initial concentration of 50 mg / L was measured and poured into two 100 mL conical flasks, and then 0.03 g of FSA was weighed in the conical flasks and covered with sealing films. The flasks were shaken at a speed of 180 rpm in a constant temperature oscillating box at 30°C for 12 hours. After adsorption, the liquid and the adsorbent were separated by suction filtration. The separated adsorbent was added to 50 mL of 0.5 mol / L HCl solution for desorption for 6 hours, and then washed with water until neutral. The washed gel beads were placed in a -80°C refrigerator for freezing for 12 hours and then placed in a -50°C freeze dryer for drying for 12 hours to obtain x-Fe-mSiO2 / SA (x represents the number of repetitions) composite microspheres. The subsequent adsorption experiment was the same as the above adsorption experiment. The specific data are shown in Table 8.
[0115] Table 8 Effect of repetition times on arsenic adsorption performance
[0116] frequency Adsorption capacity / (mg / g) Removal rate / (%) 0 78.18 96.74 1 77.14 92.57 2 76.64 91.97 3 75.54 90.64 4 74.99 89.98 5 73.36 88.03
[0117] The regeneration cycle of the adsorbent can increase its use frequency, reduce costs, and reduce the generation of byproducts. As shown in Table 8, after 5 cycles, the removal efficiency of FSA for As is still high, and the removal rate remains above 85%. This shows that FSA is an adsorbent with important reuse value and excellent performance.
[0118] Characterization results
[0119] The mSiO2 (abbreviated as mSiO2) prepared in step (2) of Example 1, the Fe-mSiO2 (abbreviated as Fe-mSiO2) prepared in step (4) of Example 1, and the Fe-mSiO2 / SA (abbreviated as FSA) prepared in step (5) of Example 1 were characterized; in addition, the material after FSA adsorbed As(V) (abbreviated as FSA-As(V)) was also characterized. The results are shown in Figure 6-Figure 9 .
[0120] Fig. 9 The SEM, TEM, AFM and EDS spectra of the adsorbent prepared in Example 1 are shown in Figures 1-3: SEM of 1-mSiO2, TEM of 2-mSiO2, SEM of 3-Fe-mSiO2; and Figures 1-7: SEM of 1-FSA, SEM of 2-FSA, AFM of 3-FSA, and EDS of 4-7-FSA.
[0121] According to the SEM images of mSiO2 and the iron-loaded mSiO2, it can be observed that mSiO2 is in the form of spherical particles with a rough surface, uniform distribution, and a porous structure. After loading, its shape remains unchanged, which can be explained that the internal structure of mSiO2 is not damaged during the iron-loading process, enabling the pores and structure of mSiO2 to be maintained. To verify the physical properties of mSiO2, TEM combined with Image-j software analysis was carried out. In the TEM images, it can be clearly observed that mSiO2 has a long-range ordered mesoporous array. After measurement, the pore diameter is about 2.89 nm and the width is about 3.93 nm, with a quite regular hexagonal pore structure, further confirming that the silica synthesized using CS belongs to mesoporous molecular sieve materials (2 nm < d < 50 nm). The uniformly distributed Fe element can be observed in the EDS spectrum of FSA, proving that iron is indeed loaded on the surface of mesoporous silica. Moreover, it can be clearly observed that the EDS energy spectrum distributions of Fe, Si, O, and As(V) after adsorption are similar, proving that during the adsorption process, As(V) is well fixed on the adsorbent surface by Fe and mSiO2, indicating the successful synthesis of Fe-mSiO2. The FSA adsorbent synthesized in this study is spherical with a diameter of 2 - 3 mm, which can effectively overcome the problems that it is difficult to carry out solid-liquid separation or the cost of solid-liquid separation is high after the action of previous adsorbents. Fig. 9 In (b), rod-like particles with square and rhombic cross-sections can be observed, and they are α-FeOOH and β-FeOOH. α-FeOOH has 4 stretching directions and belongs to the orthorhombic and rhombic crystal systems. In the structure of α-FeOOH, anions are arranged in a hexagonal close-packed manner, and each 1 Fe 3+ forms an FeO3(O)3 octahedron with its surrounding anions, and this structure has a strong attraction to As(V). β-FeOOH is a tetragonal crystal system structure, containing a monoclinic unit cell. The unit cell contains 8 FeOOHs, which are isostructural with the goethite group. The anions in the β-FeOOH structure are arranged in a body-centered cubic close-packed manner, with a lower density than α-FeOOH. The hydrogen bonds in β-FeOOH are weaker, but the length of the shortest hydrogen bond is much longer than that in H2O. It is precisely due to the existence of these different configurations of FeOOH that the adsorption capacity of Fe-mSiO2 / SA for As(V) is relatively strong.
[0122] According to Figure 6 the FT-IR spectrum, it can be seen that the peaks near 470 cm -1 , 810 cm -1 , 960 cm -1 and 1050 cm -1 are the characteristic peaks of mSiO2. Among them, the relatively weak 960 cm -1 peak is one of the typical characteristic peaks of SiO2, which is due to the vibration of the silicon-oxygen bond. At 960 cm -1A symmetrical stretching vibration peak appears at the position of Fe-mSiO2. -1 and 1650cm -1 The 470 cm-1 peak of FSA is significantly stronger than that of mSiO2, which may be due to the absorption of hydroxyl groups in water during the iron doping process to generate hydroxyl iron. -1 、810cm -1 and 1030cm -1 The absorption peak indicates that mSiO2 is well fixed on the surface of sodium alginate microspheres. -1 and 1400cm -1 An absorption peak appears near 1620cm -1 and 3400cm -1 The -OH of FSA is also weak, so it proves that FeOOH generated by Fe-O and -OH plays an important role in the adsorption process. This phenomenon can also be confirmed in the SEM spectrum: before adsorption, the surface of FSA microsphere adsorbent is covered with FeOOH particles, which disappear after adsorbing As(V), leaving a network space structure. Compared with FSA-As(V), most of the absorption peaks of FSA have not disappeared, but have been more or less weakened, proving that FSA has a better stable structure and stronger As(V) specific adsorption capacity.
[0123] according to Figure 7 From the XRD spectrum, it can be seen that the 2θ small-angle diffraction peaks of mSiO2 are (100), (110) and (200), which are consistent with the characteristics of the highly ordered hexagonal mesoporous phase of mSiO2, which is consistent with previous studies and fully proves that the mesoporous structure of mSiO2 synthesized from CS waste has been successfully constructed. From the 2θ wide angle, the intensity of the Fe-mSiO2 diffraction peak is relatively weaker than that of mSiO2, indicating that after mSiO2 is loaded with iron, the iron is evenly dispersed on mSiO2 and exists in the form of amorphous oxide, which causes the mSiO2 crystal phase to change and the intensity of the diffraction peak is affected. There is no mesoporous phase of mSiO2 in FSA, which may be because an amorphous structure is formed during the cross-linking process of Fe-mSiO2 and sodium alginate, which masks the characteristic peaks of the mesoporous phase. In addition, the individual protrusion peaks in FSA are due to the cross-linking of iron with the carboxyl groups in the sodium alginate molecules to form coordination bonds, forming a structure similar to a bridge. The protruding diffraction peak disappears after FSA adsorbs As(V) because iron and As(V) form an amorphous arsenic compound [(FeO)2AsO2], which destroys the iron complex structure formed by iron and sodium alginate, resulting in the absence of observed diffraction peaks.
[0124] according to Figure 8The XPS total spectrum of the 2p characteristic peak of Fe near 710eV shows that Fe is successfully loaded on the surface of mSiO2 and forms a relatively stable iron complex; the As3d characteristic peak at 44eV shows that As(V) is successfully adsorbed on FSA-As(V); the peak value of Si 2p spectrum is compared, and it is observed that Fe-mSiO2 is significantly weakened after cross-linking with sodium alginate, which is similar to the XRD spectrum. This is because sodium alginate is a macromolecular organic matter and usually does not cross-link with SiO2, but Fe-mSiO2 loaded with iron, in the solution, cross-links with —COOH in the sodium alginate molecule and promotes a small amount of Si to cross-link with it, forming amorphous mesoporous silica.
[0125] according to Figure 8 The XPS spectra of mSiO2 and Fe-mSiO2 are compared. After mSiO2 is loaded with iron, Si-O-Fe and Fe-OH bonds appear, indicating that the iron loaded on the surface of mesoporous silica exists in the form of FeOOH and iron oxide (Fe2O3 or Fe3O4). In order to confirm in which form Fe exists in the material, the peak fitting is performed and it is found that the Fe 2p3 / 2 orbital peak can be decomposed into two peaks near 710eV and 715eV, indicating that divalent and trivalent iron coexist in Fe-mSiO2. Combined with the O1s peak spectrum analysis, that is, γ-Fe3O4 coexists with FeOOH. Comparing the Fe 2p3 / 2 orbital peaks of FSA and FSA-As(V), the Fe 2p3 / 2 peak at 711.17eV 2+ and 714.14 eV Fe 3+ They shifted to 709.24eV and 712.12eV respectively. This is because sodium alginate forms a complex after cross-linking with iron, which leads to an increase in the outer electron density of iron, an increase in electronegativity, and a decrease in binding energy. C—O and C=O peaks were detected in the C1s spectrum, which is caused by the particularity of the molecular structure of sodium alginate. FSA's C=O at 288.73eV and C—O at 286.59eV shifted to 286.75eV and 282.89eV, and the binding energy dropped significantly. This is because -COOH first cross-links with Fe, and then forms a complex with arsenic during the adsorption process, and the binding energy drops further. As appears in the As 3d spectrum 5+ and As 3+ Some studies have shown that Fe 2+ The oxidation is accompanied by the reduction of As(V). Since γ-Fe3O4 has an inverse spinel structure, 1 / 2 of Fe 3+ Tetrahedral coordination and 1 / 2 Fe 2+ Octahedral coordination composition, Fe 3+ and Fe 2+ The adjacent positions of the cations can allow the electrons to overlap due to the Fe3+ d orbital and transitions. Under oxygen-rich conditions, γ-Fe3O4 is oxidized to γ-Fe2O3. 2+ Oxidation, vacancies appear, the compound must maintain the law of charge conservation, so the adsorbed As(V) is transferred to the Fe 2+ Or the electron reaction is reduced to As 3+ .
[0126] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. A person skilled in the art should understand that, according to the protection scope defined in the claims and the technical solution provided in this specification, multiple embodiments can be provided, all of which fall within the protection scope of the present invention.
Claims
1. A method for extracting iron and silicon from copper tailings to synthesize arsenic-adsorbing composite microspheres by self-assembly, characterized in that: The steps include: (1) copper tailings and sulfuric acid solution were mixed at a solid-liquid ratio of 1 g:10 mL, heated and stirred at 95-105° C. for 4-6 h, heating was stopped, an appropriate amount of ultrapure water was added, stirring was continued for 2-3 h, and iron source solution and acid-insoluble solid residue were obtained by suction filtration; (2) using the acid-insoluble solid residue obtained in step (1) to prepare mesoporous silica mSiO2, specifically comprising: S1: washing the acid-insoluble solid residue with water until it becomes neutral, and drying it to obtain high-silicon slag; S2: Mix high silicon slag, block NaOH and ultrapure water and place them in a high pressure reactor, heat at 155-165°C for 8-9h, filter after the reaction, and take the filtrate, i.e., Na2SiO3 solution; S3: Mix the filtrate with an aqueous solution of hexadecyltrimethylammonium bromide, adjust the pH value of the solution to 10 with an acid, and then place it in a high-pressure reactor for heating at 110-120° C. for reaction for 20-24 hours. After the reaction is completed, filter, wash with water until neutral, wash with alcohol, and dry to obtain a white powder; take the white powder and place it in a muffle furnace, and calcine it at 550° C. for 7 hours to obtain mesoporous silica; (3) preparing iron oxide using the iron source solution obtained in step (1): Add H2O2 solution dropwise to the iron source solution to remove the Fe 2+ Completely oxidized to Fe 3+ , then add ammonia water to adjust the pH value of the solution to 3.6-3.8, stir at room temperature for 0.5-1h, filter to obtain a brick red solid, and dry to obtain iron oxide; (4) Preparation of Fe-mSiO2 composite materials: Add iron oxide and mesoporous silica into dilute hydrochloric acid in a mass ratio of 4:3, perform ultrasonication for 5 minutes, stir at room temperature for 2-3 hours, filter, and dry to obtain a light yellow powder, namely, Fe-mSiO2 composite material; (5) Preparation of Fe-mSiO2 / SA composite microspheres: Add the Fe-mSiO2 composite material into ultrapure water to obtain a 1.5w / v% Fe-mSiO2 mixed solution, and dissolve sodium alginate SA in ultrapure water to obtain a 2.5w / v% SA solution; add the SA solution dropwise into the Fe-mSiO2 mixed solution under constant stirring, stir for 1.5-2h to obtain gel beads, wash with water to neutrality, and freeze-dry to obtain Fe-mSiO2 / SA composite microspheres.
2. The method according to claim 1, characterized in that: In step (4), the iron element in the Fe-mSiO2 composite material is uniformly loaded on the mesoporous silica to form a stable iron complex, and the iron element coexists in the form of γ-Fe3O4, α-FeOOH and β-FeOOH.
3. The method according to claim 1, characterized in that In step (5), the SA solution is added dropwise into the Fe-mSiO2 mixed solution at a volume ratio of 8:100; and / or The obtained Fe-mSiO2 / SA composite microspheres are three-dimensional spherical with a diameter of 2-3 mm.
4. The method according to claim 1, characterized in that In step (1), the copper tailings are sieved through a 100-mesh sieve; and / or: the concentration of the sulfuric acid solution is 4-5 mol / L; and / or: the volume of ultrapure water added is 500 mL of ultrapure water per 10-15 g of copper tailings.
5. The method according to claim 1, characterized in that In step (2), high silicon slag, block NaOH and ultrapure water are mixed in a ratio of 9 g:10 g:120 mL.
6. The method according to claim 1, characterized in that In step (4), the concentration of dilute hydrochloric acid is 0.1-0.5 mol / L; and / or: the ultrasonic power is 200W.
7. Application of Fe-mSiO2 / SA composite microspheres in removing As(V) from wastewater containing As(V), characterized in that: The Fe-mSiO2 / SA composite microspheres are prepared by the method described in any one of claims 1 to 6.
8. The use according to claim 7, characterized in that: Before the Fe-mSiO2 / SA composite microspheres are added to the wastewater containing As(V), the pH value of the wastewater is adjusted to 3-11.
9. The use according to claim 7, characterized in that: The initial concentration of As(V) in the As(V)-containing wastewater ranges from 0.1 to 50 mg / L.
10. The use according to claim 7, characterized in that: After the Fe-mSiO2 / SA composite microspheres are added into wastewater containing As(V), the adsorption time is 1-720min.
Citation Information
Patent Citations
MCM-41 ordered mesoporous material and preparation method thereof
CN110272058A
Core-shell magnetic mesoporous silica material, method for preparing material by utilizing iron tailings and application of core-shell magnetic mesoporous silica material
CN115475597A
Preparation method and application of slag-based hollow microsphere nanoreactor
CN118142526A
Cited By
Ferric oxide homogeneous and heterogeneous photoelectric self-Fenton electrode material as well as preparation method and application thereof
CN120117707A
